From Roman to early Christian Cyprus: studies in religion and archaeology - Nasrallah, Laura Salah; Luijendijk, AnneMarie; Mpakirtzēs, Charalampos N. (Wissenschaftliche Untersuchungen zum Neuen Testament, 2020)
Cover -- Titel -- Table of Contents -- Acknowledgments -- Abbreviations -- Laura Nasrallah - Introduction (and an Analaysis of Religion by Means of the Annex of Eustolios) -- Charalambos Bakirtzis - Sea Routes and Cape Drepanon: Excavations at Agios Georgios tis Pegeias, Paphos, Cyprus -- James Carleton Paget - Cyprus in the New Testament and Beyond -- Athanasios Papageorghiou and Nikolas Bakirtzis - Hagiographic Narratives and Archaeological Realities: Revisiting the Beginnings of Christianity in Cyprus -- Henry Maguire - The Gods, Christ, and the Emperor in the Late Antique Art of Cyprus -- Demetrios Michaelides - Mosaic Workshops in Cyprus from the Fourth to the Seventh Centuries CE: Two Parallel Lives? -- Andrew T. Wilburn - Ritual Specialists and the Curse Tablets from Amathous, Cyprus -- Andrew S. Jacobs - Epiphanius's Library -- Young Richard Kim - Cypriot Autocephaly, Reconsidered -- AnneMarie Luijendijk - The Gospel of Matthew in the Acts of Barnabas through the Lens of a Book's History: Healing and Burial with Books -- Ioli Kalavrezou - The Cyprus Treasures since their Discovery: A Re-Evaluation -- Stephanos Efthymiadis - The Cult of Saints in Late Antique Cyprus and the Apostolicity of its Churches: The Testimony of Greek Hagiography -- Marina Solomidou-Ieronymidou and Giorgos Philotheou - The Representation and Memory of Saints Paul, Barnabas, Epiphanios, and Others on Wall Paintings of Byzantine and Medieval Cyprus -- Bibliography -- Figures -- Subject Index.